A theoretical exploration of polyvagal theory in creative arts and psychomotor therapies for emotion regulation in stress and trauma - Haeyen, Suzanne (Frontiers in Psychology, 2024)
Polyvagal theory advocates for working with the body, becoming aware of the body and connecting with the senses. Similarly, paying attention to and influencing one's physical and sensory experience is a core aspect of the creative arts and psychomotor therapies. Polyvagal theory offers opportunities for strengthening resilience by treating emotion-regulation problems, stress, and trauma, as well as restoring regulation of the autonomic nervous system. Paying attention to and influencing physical and sensory experiences are core aspects of creative arts and psychomotor therapies. This theoretical paper explores how polyvagal theory can serve as a foundational theory and support the creative arts and psychomotor therapies for emotion regulation in stress and trauma. A number of pillars in polyvagal theory have links with arts therapies, such as an emphasis on physical and sensory experience in situations of safety or threat. This theory may offer insight into the role of the body in stressful situations, the role of co-and self-regulation, and thus the functioning of and the rationale for use of creative arts and psychomotor therapies. Through interventions focused on promoting healthy autonomic responses and regulating physiological responses, clients can learn to better regulate and process their emotional experiences. Although this could be broadly useful, it would seem particularly promising in therapies focused on stress and trauma.This article provides an introduction to polyvagal theory and outlines how it can serve as an explanatory, hypothetical model for the working mechanisms that underlie creative arts and psychomotor therapies. The application of PVT in creative arts and psychomotor therapies will be explored by describing techniques for "noticing and naming" and "learning to change," as well as by highlighting the role of PVT in the therapeutic relationship. It provides case examples and discusses the role of creative arts and psychomotor therapies for stress regulation and resilience conceptualized in line with the polyvagal theory.